Evaluating the potential footprints of land use and land cover and climate dynamics on atmospheric pollution in Pakistan - Dilawar, Adil; Chen, Baozhang; Ul-Haq, Zia; Ali, Shahbaz; Sajjad, Meer Muhammad; Junjun, Fang; Gemechu, Twekel M.; Guo, Man; Dilawar, Hamza; Zhang, Huifang; Zicheng, Zheng; Lodhi, Ehtisham (Frontiers in Environmental Science, 2024)
Evaluating the potential impacts of land use and land cover change (LULCC) and climate change on air pollution are crucial to unravel the driving forces and mechanisms behind changes in air quality. A multi-faced approach was adopted including Land change model (LCM), Mann Kendall (MK) test to evaluate the transition of land cover type, changes of climate, and atmospheric pollutants during 2004-2021 over Pakistan.Moreover, a multiscale geographically weighted regression model (MGWR) and mathematical model were used to assess the potential contribution of LULCC and climate dynamics on atmospheric pollution. It was revealed that during 2004, croplands covered an area of 9.72 × 10 4 mile 2 accounting for 38% of the total area. However, the croplands increased to 10.1 × 10 4 mile 2 , accounting for 40% of the total area in 2021.The MK test showed that the north and west-south regions significantly experienced air pollution with the increasing trend for NO2 and SO2 was 0.89× 10 15 molecules/cm 2 per year and 0.54 DU/year respectively. For climate variability, mean precipitation (Precp) and mean surface pressure (SP) showed a prominent increasing trend with a maximum value of 1 mm/year and 0.01 Kpa/year respectively. Mean temperature maximum (Tmax) showed an increasing and decreasing trend, with the highest value of 0.28 ˚C/year and 0.08 ˚C/year respectively. In the context of contribution, the conversion of cropland to grasslands increased the trend for SO2 concentrations. The highest increasing trend 1.5 DU for O3 was found due to conversion of grasslands to shrublands. Additionally, regional climate played a significant role in making air pollution stagnant across the country. Precp and wind speed (WS) contributed highly to escalating NO2 in Pakistan, while Precp showed the highest contribution value (0.004 DU) to increase SO2 concentrations. For O3, the most influential climate factor was Precp. These results on a long-term temporal scale demonstrated how maintaining climate variability through comprehensive land use management can help to improve ambient air quality in Pakistan.